Debt covenant slack and ex-post conditional accounting conservatism. Issue 2 (23rd February 2020) - Kim, Bong Hwan
Abstract : This study examines how conditional accounting conservatism varies after debt contracts are executed (ex-post conditional conservatism) depending on the closeness to violations of debt covenants, the costs of covenant violations, and bank monitoring. I hypothesise that borrowers with lower debt-covenant slack have an incentive to avoid covenant violations and will have lower ex-post conditional conservatism levels than those with higher slack. I find that borrowers with both lower and higher slack increase their ex-post conditional conservatism, but that the magnitude of this increase in conservatism is positively associated with the level of covenant slack. Further, this positive relationship between the ex-post change in conditional conservatism and the debt-covenant slack is more pronounced when the costs of the debt-covenant breach are greater, and is less pronounced when lenders have stronger incentives to monitor borrowers. This study provides evidence that the ex-post change in conditional conservatism is affected by the costs of a covenant breach and bank monitoring.